Hikmat berdiri Sebagai Hukum Perjanjian: Solusi Alternatif untuk Penyelesaian Sengketa Keuangan menurut Amsal 6:1-5 - Manurung, Well Therfine Renward; Sualang, Farel Yosua (Sekolah Tinggi Teologi Transformasi Indonesia, 2023)
Abstract: Proverbs is a book which contains wisdom and is a very important book in the Old Testament besides the other books of wisdom. An important piece of wisdom in Proverbs 6:1-5 is the practical advice regarding an inexperienced person becoming a guarantor for others, thereby exposing himself to risks such as financial ruin, poverty or even debt. This research uses qualitative terms such as: analysis from the perspective of biblical theology, exegesis with an interpretative approach (interpretative design), specifically thematic study, in order to explore and obtain the meaning of words and the implementation of the phrases